Group Recommender System Using Hybrid Method - Esa Alfitrassalam; Ade Romadhon; Z K Abdurahman Baizal (STMIK Budi Darma, 2021)
In our daily activities, we make a lot of decisions either individually or in groups. The recommender systems is a solution for making decisions. One of the most common recommender systems is the recommendation for tourist destinations, where a number of tourist attractions are given as tourist attractions that are recommended to be visited by someone. There are still few recommended tourist attractions that provide recommendations for a group, while there are several tourist attractions that are more suitable if visited by several people at the same time. In this study, a recommender system for tourist attractions in Bandung-Raya Regency is proposed which is given to user groups. The recommended method used is Hybrid Collaborative Filtering and Knowledge-Based Filtering. In the process of selecting groups that are candidates to be recommended to users, Borda calculations are carried out with votes so that users can determine whether they like or dislike and match or not match the recommender generated by the system. The results of the evaluation of experiments conducted by taking surveys of users showed an average value. the average of the indicators of user satisfaction with the results of group recommender is 4.4 on the scale (1-5)